Assessing outdoor thermal comfort and its relation with commuting behaviour in Jurong Lake District - Jahja, Gladys Isabel (2017)
With rapid urbanisation and persisting climate change, outdoor thermal comfort in urban spaces can be jeopardised by a lack of proper and careful urban planning. This is especially relevant for Singapore which continuously undergoes urbanisation for the country’s economy and improvement of quality of life. While numerous thermal comfort studies have focused on the indoor environment, outdoor thermal comfort is also proven to have prominent effect on the liveability of urban cities. This is especially important for the context of Singapore where public transport and walking are the top transport choice. This paper presents studies on outdoor thermal comfort based on a field survey conducted in Jurong Lake District (JLD), Singapore, prior to and as a preparation for its upcoming development plan. Outdoor thermal comfort was evaluated based on thermal sensations and commuting behaviour using microclimatic parameters and field questionnaire survey method. Thermal comfort factors evaluated include thermal sensation, humidity sensation, wind sensation and sun sensation while commuting behaviour evaluated include factors such as mode of transport and shelter coverage throughout the commuting path. Findings from the survey conducted with a total of 131 residents of JLD are presented. The findings include: (1) sun sensation to be the most significant factor affecting thermal comfort, (2) walking and bus to be the current most used mode of transport in JLD and that (3) only partial shelter coverage is currently available. There are also significant correlations found: (1) between thermal as well as wind sensation vote and the different commuting paths, (2) between wind sensation and mode of transport and (3) between sun sensation and shelter coverage. Based on these findings, one can conclude that evaluating outdoor thermal condition is necessary for the planning of urban spaces, and that commuting behaviour is indeed a relevant factor for considerations when studying outdoor thermal comfort.